Temporal evolution of primary angiitis of the central nervous system (PACNS) on MRI following immunosuppressant treatment - Wagner, Franca; Almeida, Gonçalo G.; Willems, Erik P.; Weber, Johannes; Geiss, Johannes; Hundsberger, Thomas; Mordasini, Pasquale; Wildermuth, Simon; Leschka, Sebastian; Waelti, Stephan; Dietrich, Tobias Johannes; Fischer, Tim Steffen (Insights into imaging, 2024)
Purpose To systematically analyse the time course of vessel wall enhancement and associated stenosis in patients with primary angiitis of the central nervous system (PACNS) following immunosuppressive therapy. Material and methods Two neuroradiologists retrospectively analysed MRIs of patients with PACNS seen at the Bern University Hospital and the St. Gallen Cantonal Hospital between 2015 and 2020. MRIs were examined for the presence of vessel wall enhancement, length of vessel wall enhancement (mm), circumferential extent of enhancement (degree) and degree of stenosis (%). Descriptive statistics and measurements of interobserver reliability were obtained. To investigate the temporal profiles of the variables following the commencement of immunosuppressant treatment, four series of Bayesian generalised multi-level models were generated. Results A total of 23 patients with 43 affected vessels identified from 209 MRI exams were evaluated (mean follow-up: 715 days, standard deviation ± 487 days), leading to a complete dataset of 402 entries. Vessel wall enhancement and circumferential extent of enhancement decreased for approximately 1 year after the initiation of immunosuppressant therapy. Changes were more pronounced in younger patients. Disappearance of vessel wall enhancement (in at least one vessel) was seen in about half of patients after a median of 172 days interquartile range 113–244, minimum 54 days, maximum 627 days. Conclusions This study evaluated the typical time course of vessel wall enhancement in patients with PACNS. Our results could be a useful reference for radiologists and clinicians interpreting follow-up imaging in patients with PACNS. Critical relevance statement Routine clinical exams can be interpreted with more confidence when radiologists are aware of the typical temporal evolution of vessel wall enhancement in patients with primary angiitis of the central nervous system after initiation of immunosuppressive therapy. Key Points Few data exist for vessel wall imaging of primary angiitis of the central nervous system. Following immunosuppressant therapy, vessel wall enhancement decreases for approximately one year. These results may serve as a reference for radiologists performing follow-up imaging. Graphical Abstract